2021
DOI: 10.21827/jve.4.35981
|View full text |Cite
|
Sign up to set email alerts
|

Fostering intercultural competence through videoconference exchange: using an external provider to match learners with trained native speakers and administer video calls

Abstract: This practical case presents the use of an External Provider (EP) as an alternative approach to the traditional telecollaboration setting where a partnership with a foreign higher education institution is established. Usually, these partnerships involve language exchanges between learning partners who mutually practice each other’s native language. Instead, an eight-week cross-cultural Virtual Exchange (VE) in Spanish between US college students studying Spanish and trained Colombian university students was or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Looking back on over 20 years' experience and scholarship, VE is recognised today as a convincing way of pursuing various goals in the classroom in addition to the promotion of FL skills, such as foster-ing intercultural competence (Lenkaitis, Calo & Venegas Escobar 2019;Varo Varo 2021), intercultural communication skills (Belz & Müller-Hartmann 2003) and culture-specific awareness (Curtindale, Krylova & Minyurova 2020). In a recent study, Nishio, Fujikake and Osawa (2020) found that in addition to learning FL skills, the motivation to learn a foreign language was improved as the social process itself revealed personal significance and increased desire to learn.…”
Section: Introductionmentioning
confidence: 99%
“…Looking back on over 20 years' experience and scholarship, VE is recognised today as a convincing way of pursuing various goals in the classroom in addition to the promotion of FL skills, such as foster-ing intercultural competence (Lenkaitis, Calo & Venegas Escobar 2019;Varo Varo 2021), intercultural communication skills (Belz & Müller-Hartmann 2003) and culture-specific awareness (Curtindale, Krylova & Minyurova 2020). In a recent study, Nishio, Fujikake and Osawa (2020) found that in addition to learning FL skills, the motivation to learn a foreign language was improved as the social process itself revealed personal significance and increased desire to learn.…”
Section: Introductionmentioning
confidence: 99%